Anomalous results using countercurrent immunoelectrophoresis for the detection of pneumococcal antigen in Bactec blood culture media. - Chiang, W C (1984)
On examination of Bactec blood cultures for pneumococcal antigen by countercurrent immunoelectrophoresis the consistent presence of a non-specific protein band caused problems with the interpretation of results, even in laboratories experienced in performing countercurrent immunoelectrophoresis. When the Bactec blood culture system is used, countercurrent immunoelectrophoresis should not be relied on for the detection of pneumococcal antigen.